2021
DOI: 10.1111/spsr.12491
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of Radical Right‐wing Populist Parties in Western European Governments – A Comparative Analysis

Abstract: More and more Western European radical right‐wing populist parties participate in the governments of their respective countries. At least some of these parties moderate—that is, become less radical—once they join the government; others, however, do not. Although the literature has addressed such moderation, the conditions that lead to it have not been analyzed comprehensively. In this paper, we use a fuzzy‐set qualitative comparative analysis (fsQCA, N = 14) to determine what conditions are consistently associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…But the comparison between the two situations, rather than a mainstreaming of authoritarianism, can probably be better understood in the context of a very different political scenario. While populist parties in general have indeed mainstreamed, in Western Europe, this has meant that all PRRP – with the notable exception of the Swiss Schweizerische Volkspartei (SVP), operating in a very peculiar institutional system – have moderated in government (Capaul and Ewert, 2021).…”
Section: From Opposition To Government: Identity Pragmatism and The M...mentioning
confidence: 99%
“…But the comparison between the two situations, rather than a mainstreaming of authoritarianism, can probably be better understood in the context of a very different political scenario. While populist parties in general have indeed mainstreamed, in Western Europe, this has meant that all PRRP – with the notable exception of the Swiss Schweizerische Volkspartei (SVP), operating in a very peculiar institutional system – have moderated in government (Capaul and Ewert, 2021).…”
Section: From Opposition To Government: Identity Pragmatism and The M...mentioning
confidence: 99%
“…While 'inclusion-moderation' theories (Tepe 2019) suggest a moderating effect, other empirical findings present a more nuanced picture (Akkerman et al 2016;Caiani and Graziano 2022;Zulianello 2019). They demonstrate that de-radicalization is not an automatic process but depends on multiple factors, such as the party's political tradition and strategies (Albertazzi and McDonnell 2010;Bartha et al 2020), internal organization and leadership (Bernhard 2020;Zaslove 2012) and the power balance between radical and mainstream forces in coalitions (Askim et al 2022;Capaul and Ewert 2021).…”
Section: Access To Power and Mainstreaming Between National And Localmentioning
confidence: 99%
“…The 'inclusion-moderation' thesis might suggest that electoral success and inclusion in political systems might trigger processes of moderation and mainstreaming (a term that underlines the relative nature of 'moderation' within a wider political system) (Akkerman et al, 2016). However, studies have shown that moderation does not or only partially occurs (Akkerman & Rooduijn, 2015;Capaul & Ewert, 2021). Mainstreaming does not occur on parties' radical ideological positions but is visible in the tempering of anti-establishment attitudes and extreme right reputations (Akkerman et al, 2016: 276-278).…”
Section: Between-party Differences: the Effect Of National Contextmentioning
confidence: 99%
“…The party's framing of Muslims as a cultural out-group was further illustrated by campaigns for the ban on minarets in 2009, against facilitated naturalization in 2017, and for a ban on concealment in 2020. In this context, the SVP's front stage performance (Wodak, 2015) conveys both the impression of a euphemistic care about the Swiss economy and Swiss identity without being moderate in its demands (Capaul & Ewert, 2021).…”
Section: Description Of 'Good' and 'Bad' Migrantsmentioning
confidence: 99%
See 1 more Smart Citation